2023
DOI: 10.1128/spectrum.03135-22
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Integrated Multi-Omics Approach To Identify Molecular Mechanisms and Critical Factors Involved in the Pathogenesis of Leptospira

Abstract: Leptospirosis is a zoonotic disease of global importance. It is caused by a Gram-negative bacterial spirochete of the genus Leptospira .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 104 publications
0
11
0
Order By: Relevance
“…Concerning the diderm envelope, lipoproteins are abundant in all subcellular compartments, including the periplasmic leaflet of IM, OM, and the surface of OM, which puts the focus squarely on how this set of proteins reaches the outer leaflet of the OM upon exposure to environmental cues. Leptospira , like other spirochetes, possesses a sec-dependent protein translocation system named T2SS, which is not found in Borrelia and Treponema , and could also utilize it to secrete surface lipoproteins that are partially unfolded proteins. , Our proteomics analysis showed an increase in TolC family proteins (LIC_11941, LIC_12575, and LIC_12693), which create trans periplasmic channels in the type I secretion system. , In the type II secretion system of L. interrogans (PATH:lic03070), Gsp proteins are crucial in releasing toxins and cell wall-degrading enzymes. , The current study identified GspC, GspG, GspD, GspN, and GspE. In response to the physiological conditions of infection, upregulation of orthologs (YajC, SecG, SecF, SecA, SecD, and signal peptidase I) of the Sec-translocation system was observed on the outer membrane, with YajC and signal peptidase I being notably significant (PATH:lic03060).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Concerning the diderm envelope, lipoproteins are abundant in all subcellular compartments, including the periplasmic leaflet of IM, OM, and the surface of OM, which puts the focus squarely on how this set of proteins reaches the outer leaflet of the OM upon exposure to environmental cues. Leptospira , like other spirochetes, possesses a sec-dependent protein translocation system named T2SS, which is not found in Borrelia and Treponema , and could also utilize it to secrete surface lipoproteins that are partially unfolded proteins. , Our proteomics analysis showed an increase in TolC family proteins (LIC_11941, LIC_12575, and LIC_12693), which create trans periplasmic channels in the type I secretion system. , In the type II secretion system of L. interrogans (PATH:lic03070), Gsp proteins are crucial in releasing toxins and cell wall-degrading enzymes. , The current study identified GspC, GspG, GspD, GspN, and GspE. In response to the physiological conditions of infection, upregulation of orthologs (YajC, SecG, SecF, SecA, SecD, and signal peptidase I) of the Sec-translocation system was observed on the outer membrane, with YajC and signal peptidase I being notably significant (PATH:lic03060).…”
Section: Discussionmentioning
confidence: 92%
“…According to our proteomic analyses, numerous proteins involved in metabolic pathways have been altered, suggesting that metabolic gene expression has been reprogrammed to adapt to host environmental changes. Leptospira breaks down long-chain fatty acids instead of glucose or other carbohydrates in the host environment. , It necessitates the expression of fatty acid metabolism proteins (LIC_11630, LIC_11618, LIC_13301, LIC_10974, LIC_20064, LIC_20065). Bacteria may also lower their oxygen requirement during host-cell interaction by downregulating oxidative phosphorylation proteins, including cytochrome oxidase subunits, NADH dehydrogenase, etc .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations